Control of rice blast disease caused by Magnaporthe oryzae by application of antifungal nanomaterials from Emericella nidulans - Jiao Jiao Song; Kasem Soytong; Somdej Kanokmedhakul (My University, 2021)
Control of rice blast disease caused by Magnaporthe oryzae by application of antifungal nanomaterials from Emericella nidulans | Jiaojiao Song, Kasem Soytong, Somdej Kanokmedhakul | Agricultural Journals
Keywords: Blast disease; Magnaporthe; Disease Control; Plant-Microbe Interactions and Immunity